The proinflammatory soluble CD40 ligand is associated with the systemic extent of stable atherosclerosis - Pereira-Da-silva, Tiago (2021)
Funding: T.P. has received research support from Fundação para a Ciência e Tecnologia, Portugal [Project UID/BIO/04565/2020], and Programa Operacional Regional de Lisboa 2020 [Project N. 007317].